Usability evaluation successful factors (SFs) framework through entrepreneurship program at community college Malaysia: modified norminal group technique approach - Madar, Ahmad Rizal; Abd. Hamid, R. (Universiti Putra Malaysia Press, 2017)
This paper discusses the success factors (SFs) of the entrepreneurship programme available in Malaysian community colleges. The benefit of the Modified Nominal Group Technique (NGT) approach carried out aims to achieve understanding of the usability test and evaluation of the SFs framework. The objective of this study is to identify the usability and evaluation of lecturers on the elements of entrepreneurship for four domain areas, strategy, environment, temporal and industry. The analysis covers the importance of SFs framework development, which determines the type of framework to use as reference in carrying out the entrepreneurship programme in Malaysian community colleges. In the usability test and evaluation process, 21 experts were chosen from three types of community college, from whom seven lecturers were allocated to each programme based on the understanding of the lecturers. Questionnaires were distributed to seek lecturer consensus. The Statistical Package for the Social Sciences (SPSS) version 22.0 was used to analyse and find the percentage of consensus for each domain within the framework. This was to find the percentage of expert consensus against the SFs framework. The result of the analysis shows more than 75% acceptance and consensus for the functionality of SFs. Basically, this analysis is capable of providing reference and guidelines for the development of a SFs framework. Therefore, the analysis is able to provide information and reference for future researchers to explore the domain of entrepreneurship.